Struggle against the state social network and protest mobilization in India - Swain, Ashok (Ashgate Pub., 2010)
Many developing countries pursue policies of rapid industrialization in order to achieve faster economic growth. Some policies cause displacement forcing many individuals to take up a fight against the state. This title demonstrates how displaced people mobilize to protest with the help of their social networks.